2020
DOI: 10.3390/v12091023
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Infections in Companion Animals: Virology, Epidemiology, Clinical and Pathologic Features

Abstract: Coronaviruses are enveloped RNA viruses capable of causing respiratory, enteric, or systemic diseases in a variety of mammalian hosts that vary in clinical severity from subclinical to fatal. The host range and tissue tropism are largely determined by the coronaviral spike protein, which initiates cellular infection by promoting fusion of the viral and host cell membranes. Companion animal coronaviruses responsible for causing enteric infection include feline enteric coronavirus, ferret enteric coronavirus, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
26

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 147 publications
1
87
0
26
Order By: Relevance
“…Serum samples from the pre–COVID-19 cohort were tested against SARS-CoV-2 antigens to screen for potential cross-reactive antibodies elicited by endemic coronaviruses in cats and dogs because they are natural reservoirs of several coronaviruses (i.e., FCoV [genus Alphacoronavirus ] in cats, canine coronavirus [CCoV; genus Alphacoronavirus ] and CRCoV [genus Betacoronavirus ] in dogs) ( 20 , 22 , 23 ). We summarized sequence identities of SARS-CoV-2 antigens used and matching endemic coronavirus antigens ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Serum samples from the pre–COVID-19 cohort were tested against SARS-CoV-2 antigens to screen for potential cross-reactive antibodies elicited by endemic coronaviruses in cats and dogs because they are natural reservoirs of several coronaviruses (i.e., FCoV [genus Alphacoronavirus ] in cats, canine coronavirus [CCoV; genus Alphacoronavirus ] and CRCoV [genus Betacoronavirus ] in dogs) ( 20 , 22 , 23 ). We summarized sequence identities of SARS-CoV-2 antigens used and matching endemic coronavirus antigens ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, SARS-CoV-2 (a betacoronavirus) and FCoVs (alphacoronaviruses) are taxonomically distant and their N proteins share only 26% amino acid identity and 44% amino acid similarity. Regardless, in order to evaluate the potential seroprevalence of FCoVs in our cat sera and to determine the potential cross-reactivity of the coronavirus antibodies, we used commercial [43,44], and is at a much higher percentage than that of antibodies against the SARS-CoV -2's N protein (7.9%). Taken together, these data suggest that the SARS-CoV-2 N-based ELISA can specifically detect N-specific IgG antibodies that are unlikely to be cross-reactive with the anti-FCoV antibodies in these cats.…”
Section: Screening Feline Serum Samples By Fipv-based Elisamentioning
confidence: 99%
“…A new strain of CCoV-IIa (CB/05) has been shown to be able to cause a fatal disease characterised by systemic spread of the virus (Decaro et al 2008a ), and in recent years, an increasing number of reports of infections by this new highly virulent pantropic virus (pCCoV) have also been documented in puppies and in a wolf. Infection is characterised by fatal multisystemic illness with lethargy, inappetence, vomiting, haemorrhagic diarrhoea, lymphopenia, ataxia, and seizures (Alfano et al 2019 ; Haake et al 2020 ; Licitra et al 2014 ). However, several studies have demonstrated that this pantropic strain can also associate to subclinical infections and/or to the decrease of lymphocyte counts, rather than to severe clinical signs and death (Marinaro et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%